Beyond corporal punishment : teachers' perceptions and suggested alternatives to the abolishment of corporal punishment in South African schools. - Molepo, Nono (My University, 2010)
This study investigated educators’ perceptions on the abolishment of corporal punishment. Three quarters of the educators in the study were not in favour of the abolition of corporal punishment and gave their reasons for this view. Corporal punishment emerged as an enduring disciplinary strategy used by educators in spite of its ban. Legislation and litigation did not seem to be effective deterrents. Those who supported the abolition of corporal punishment were equally worried about what they perceived to be an absence of effective methods in maintaining classroom discipline. The educators saw a need to train in maintaining discipline at school. This study also examined literature on corporal punishment, alternatives to this method and made recommendations.